Cross Cultural Consumers Perceptions of Country-of-Origin and Luxury Brands - Handini Audita; Michael Marck (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
Understanding consumer behavior in the luxury industry is important. The extant literature suggests that cross-cultural conditions reflect the existence of differences in behavior and perceptions of consumers. This research investigated the way consumers in different countries and cultures perceive the country-of-origin concept in the luxury sector and also their perception about luxury brands itself. The purpose of this research was to investigate how the perception of the country-of-origin concept and the concept of luxury brands differs across nations. The value of this research is to provide empirical evidence describing how the different perceptions of country-of-origin issues and luxury brands contribute in the development of the fashion luxury brands industry. This quantitative research utilized online questionnaires attended by 190 respondents distributed from June 2012 to July 2012. Questionnaires were distributed online to different nation groups. The findings of the research indicate two interesting outcomes. First, for the case of fashion luxury brands, there were no significant differences of perceptions among the nation group perceptions regarding the country-of-origin concept. Second, there were significant differences of perceptions among the different nation group perceptions regarding to the luxury brand concept.